-x+26=2x-10
+x +10 +x +10
36+3x
divde by 3
12=x
m∠D=2(12)-10
=24-10
=14
Answer: 21 & 18
Step-by-step explanation:
Sum of two numbers is 39
Difference is 3
Let the numbers be x & y
X+y=39........equation 1
X-y=3...........equation 2
X=3+y............equation 3
Substitute equation 3 into equation 1
(3+y)+y=39
3+y+y=39
3+2y=39
2y=39-3
2y=36
Y=36/2
Y=18
Substitute for y in equation 2
X-y=3
X-18=3
X=3+18
X=21
The two numbers are 21 & 18
10-5=5 and 16-10=6 then you multiply 6x5
the answer is 30 Because you have to multiply L x W
The given equation of the ellipse is x^2
+ y^2 = 2 x + 2 y
At tangent line, the point is horizontal with the x-axis
therefore slope = dy / dx = 0
<span>So we have to take the 1st derivative of the equation
then equate dy / dx to zero.</span>
x^2 + y^2 = 2 x + 2 y
x^2 – 2 x = 2 y – y^2
(2x – 2) dx = (2 – 2y) dy
(2x – 2) / (2 – 2y) = 0
2x – 2 = 0
x = 1
To find for y, we go back to the original equation then substitute
the value of x.
x^2 + y^2 = 2 x + 2 y
1^2 + y^2 = 2 * 1 + 2 y
y^2 – 2y + 1 – 2 = 0
y^2 – 2y – 1 = 0
Finding the roots using the quadratic formula:
y = [-(- 2) ± sqrt ( (-2)^2 – 4*1*-1)] / 2*1
y = 1 ± 2.828
y = -1.828 , 3.828
<span>Therefore the tangents are parallel to the x-axis at points (1, -1.828)
and (1, 3.828).</span>
Answer:
$8.85
Step-by-step explanation: